Profiting from Family Systems Theory in Family Businesses - Lea, Schuhmacher; Jurek, Martin; Machek, Ondřej, 1985-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This master’s thesis aims to uncover if family businesses can profit from family systems theory and its practices, especially in times of conflict and change. It discovers the conflicts and times of change family businesses face and the methods of systems theory being applied to practice. The qualitative research, in the form of nine interviews with different groups of interest, ranging from consultants to family business owners, gave a diverse perspective on the matter. The research revealed that family businesses can profit from systems theory, but not all methods discussed in theory are being put to practice. Developing a systems thinking mindset is beneficial for family businesses, however, many traditional family businesses lack awareness about systems theory and its underlying effects on the business.
Vedoucí práce: Martin Jurek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses